Upaya Peningkatan Pengetahuan Pasien dan Keluarga tentang Manajemen Keperawatan Intraoperatif untuk Keselamatan Pasien - Andang Sudarmono; Mustika Sari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Patient safety during intraoperative procedures is a top priority in nursing services in the operating room. However, patient and family understanding of intraoperative nursing management is still limited, which can have an impact on patient readiness before undergoing surgery. This community service activity aims to improve patient and family knowledge about the important role of intraoperative nursing in maintaining patient safety. The method used is an educational approach through interactive counseling delivered directly to patients and families in the pre-operative room. The material includes patient safety standards, the role of nurses during surgical procedures, and the importance of effective communication between the medical team, patients, and families. Evaluation was carried out by comparing the level of understanding before and after education using a simple questionnaire. The results showed a significant increase in understanding, seen from changes in patient attitudes and readiness to face surgical procedures. Appropriate and easy-to-understand education has been shown to be effective in supporting active participation of patients and families, as well as encouraging the creation of a safer surgical environment.